KEPENTINGAN POLITIK MASYUMI DALAM TAFSIR ANNUR KARYA TENGKU MUHAMMAD HASBI ASHSHIDDIEQY - Abd Rahman; Suci Wulandari (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2019)
This study aims to look at aspects of Masyumi's political interests that sparked the spirit of the Islamic State in Annur's interpretation of Hasbi Ashshiddieqy. Using the socio-political analysis approach this study shows that Hasbi's interpretation in Annisa (4): 58-59 carries the political interests of the Masyumi which is aspired to the Islamic State. In this case Hasbi interprets that meant by ulu alamr in this verse is ahl halli wa alaqdi, the legislatif and eksekutif leaders according to the constitution at that time. Although carrying Islam as the basis of the state, Hasbi did not reject the meeting of Islamic teachings and Pancasila within the framework of the nation state. The interests carried by Hasbi are inseparable from his role as a reformist figure and Masyumi's representative in the constituents. This also confirms that a product of interpretation cannot be completely separated from the interests of the interpreter, it can even be a reflection of the political interests of its time